If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 9 = 2x + 27 Reorder the terms: 9 + -4x = 2x + 27 Reorder the terms: 9 + -4x = 27 + 2x Solving 9 + -4x = 27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + -4x + -2x = 27 + 2x + -2x Combine like terms: -4x + -2x = -6x 9 + -6x = 27 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + -6x = 27 + 0 9 + -6x = 27 Add '-9' to each side of the equation. 9 + -9 + -6x = 27 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 27 + -9 -6x = 27 + -9 Combine like terms: 27 + -9 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| 8r-(-8+6r)=2 | | 1=-(1+5x)-8x | | 1/5x=7-4/5x | | 11=711 | | -3(-9k+3)=-(4+3k) | | x-7/2=10-4x | | 230-4x=32x+18 | | 5a^2+55ab+150b^2=0 | | 6a+4a-5=7a-23 | | 2014-1997=x | | 1/2(16y+6)=19 | | 3(t-1)=18 | | -52(-2)=x | | 56/-2=x | | -56/2=x | | (4x/9)+7=31 | | -10=-7z-(-9z+3) | | -3=4z-(9z+2) | | -56/-2=x | | 8^1/3+15=x | | 4x/9+7=31 | | 3(x-2)+5=11 | | -2(-10n+2)=-(2-10n)+5n | | ((2x+5)/(x-3))-1 | | -3x+5(2x-4)=-8-5x | | 4(4x-3)=3(3x+2) | | 4x+3-2x=17 | | m^2x^2+n^2=0 | | 5-2x/4=-9 | | 7-2m=15 | | 3x^2+8x=8 | | 3(6x+3)=5(2x-5) |